Rangkaian Close-Up, Ekspresi Visual Ritual Tiban: Wujud Pengorbanan Dalam Film Eksperimental - Sadewa, Ghalif Putra (Jurusan Seni Rupa ISBI Bandung, 2022)
ABSTRACTTiban is a sacred performing art in Blitar, this tradition is trusted by the community to request rain during the dry season. The offerings, the spells, the calculation of days and the places of execution are considered necessary as a complement to traditional ceremonies. The culmination of Tiban's ritual is the sacrifice of citizens in the whip battle. But unfortunately, visibility is one of the factors that causes changes in the offender's emotions to become opaque. Visual expression of sacrifice is a manifestation of the realization of individual feelings, spontaneous, and emotional in interpreting rituals. Therefore, a close-up was chosen as a medium to closely observe the faces of Tiban participants. Close-up creates intimacy between characters, moves forward grooves or highlights details so the audience understands the moment in the ritual. This shot will simultaneously affect the structure and content of making experimental films. The close-up arrangement as a story style raises tension that focuses on the aesthetic aspects of the object of creation. The face shot provoked to show details that were previously ignored. Visual close-up is no longer a simple representation of reality, but imagery becomes a unit that creates atmosphere, defines character, intensifies the situation, and increases symbol status in the use of mise en scene as a plot. The aim is to produce meaning, emotion, rethink, while presenting a new perspective.Keywords : experimental, close-up, face expression, ritualABSTRAKTiban adalah seni pertunjukkan sakral di Blitar, tradisi ini dipercaya masyarakat guna memohon hujan saat musim kemarau. Sesaji, mantra, perhitungan hari serta tempat pelaksanaan dipandang perlu sebagai pelengkap upacara adat. Puncak dari ritual Tiban adalah pengorbanan warga dalam adu cambuk. Namun sayang, jarak pandang menjadi salah satu faktor penyebab perubahan emosi pelaku menjadi kabur. Visual ekspresi pengorbanan merupakan bentuk realisasi dari perasaan individu, spontan, dan emosional dalam memaknai ritual. Oleh karena itu, close-up dipilih sebagai medium untuk mengamati secara dekat wajah peserta Tiban. Close-up menciptakan keintiman antar karakter, menggerakkan alur ke depan atau menyoroti detail sehingga penonton memahami momen dalam ritual. Bidikan ini sekaligus akan memengaruhi struktur dan konten dalam penciptaan film eksperimental. Rangkaian close-up sebagai gaya penceritaan, menimbulkan ketegangan yang menitikberatkan kepada aspek estetik objek ciptaan. Close-up pada wajah, memprovokasi untuk menunjukkan detail-detail yang sebelumnya terlewatkan oleh pandangan. Visual dari rangkaian close-up bukan lagi representasi gambar sederhana dari realitas, tetapi gambar itu menjadi satu kesatuan yang menciptakan atmosfer, mendefinisikan karakter, mengintensifkan situasi, dan mengangkatnya ke status simbol dalam penggunaan pemanggungan (mise en scene) sebagai alur. Tujuannya menghasilkan makna, emosi, pemikiran ulang, sekaligus menyuguhkan cara pandang baru.Kata Kunci: eksperimental, close-up, ekspresi wajah, ritual